The effect of the environmental management system on the clean production strategy / case study in Middle Refineries Company - عبد حسن رسل سعد; احمد يوسف عبد الاله (Journal of Economics and Administrative Sciences, 2020)
The aim of this research is to measure and analyze the gap between the actual reality and the requirements of the environmental management system in the middle refineries company/refinery cycle according to ISO14001: 2015, as well as to measure the availability of a clean production strategy and test the relationship and impact between the availability of the requirements of the standard and a clean production strategy for the actual reality in the company. The research problem was determined by the extent to which the requirements of the environmental management system are applied according to ISO14001: 2015 in the middle refineries company? To what extent are the required clean production strategies available in the company? What is the nature of the relationship and influence between them? In order to reach the scientific facts, the research used a case study approach which includes relying on a checklist in collecting data and information on the items of ISO14001: 2015 and clean production strategy, in addition to personal interviews, observation, field coexistence, and relying on documents and records related to research as a tool. Using a number of statistical methods represented by weighted mean and percentage of conformity to diagnose the gap between the application of the requirements of the environmental management system in accordance with the international standard ISO14001: 2015 and the strategy of clean production between The actual production for both, as well as utilizing simple linear regression coefficient, correlation coefficient and the coefficient of determination test (t) test (f) in order to test hypotheses and morale between the variables of the study and testing of (LSD) to determine the average differences between the two samples. A number of results, the most important of which is that the researched company has a weakness in the application of ISO 14001 and the researchers noted that the reason for this is due to the lack of financial allocations and limited qualified human resources in the field of application of the standard and also a weakness in the company’s knowledge of applying a clean production strategy. In addition, the company does not have any clean environmental strategies. And a number of recommendations, the most important of which is that the senior management of the company must work to provide the financial allocations necessary to implement the ISO14001 standard and focus on qualifying human resources to be able to apply the environmental management system according to the requirements of the standard and the company should also study the clean production strategy because of its great importance in Improve the environmental reality of the company.